2022
DOI: 10.1212/wnl.0000000000200261
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy

Abstract: Background and Objectives:In patients with lobar intracerebral hemorrhage(ICH) etiological characterization represents a trade-off between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy(CAA).Methods:This external validation analyzed 210 consecutive patients with lobar ICH and available CT&MRI studies from a prospective single-center observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…5 Another limitation is the interrater reliability of finger-like projections detection, a concern directly addressed by the Edinburgh group through an online training tool. Sembill et al 6 reported only moderate interrater agreement for finger-like projections (Cohen kappa of 0.66 vs 0.80 for SAH and 0.81 for the Boston criteria diagnosis), similar to that in the original publication.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…5 Another limitation is the interrater reliability of finger-like projections detection, a concern directly addressed by the Edinburgh group through an online training tool. Sembill et al 6 reported only moderate interrater agreement for finger-like projections (Cohen kappa of 0.66 vs 0.80 for SAH and 0.81 for the Boston criteria diagnosis), similar to that in the original publication.…”
supporting
confidence: 68%
“…This possibility is supported by the observed association of SAH with cSS, 6 an imaging finding linked to severe leptomeningeal CAA and vascular degeneration. 7 Sembill et al 6 also noted association between cSS and finger-like projections, an ICH feature that is not understood at a mechanistic level but also potentially a reflection of bleeding from a leptomeningeal source.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“… The simplified Edinburgh criteria are based on analysis of the non-contrast CT. ( Rodrigues et al, 2018 ) In the original study, ( Rodrigues et al, 2018 ) no patients had fingerlike projections in isolation, but given the association between CAA and fingerlike projections, fingerlike projections in isolation were (in line with previous studies) ( Schwarz et al, 2022 , Sembill et al, 2022 ) categorized as medium risk. …”
Section: Introductionsupporting
confidence: 59%
“…Neuroimaging with Computed Tomography (CT) or Magnetic Resonance Imaging (MRI) can reveal characteristics suggestive of CAA. The simplified Edinburgh criteria ( Table 1 ) ( Rodrigues et al, 2018 , Schwarz et al, 2022 , Sembill et al, 2022 ) and the modified Boston criteria ( Table 2 ) ( Smith and Greenberg, 2003 , Linn et al, 2010 , Greenberg and Charidimou, 2018 ) evaluate and categorize these features to make a clinical diagnosis of CAA when tissue analysis is lacking. Validation studies of these criteria against histopathological evidence revealed 88–100% specificity for ruling in “high risk CAA” and “probable CAA” ( Rodrigues et al, 2018 , Greenberg and Charidimou, 2018 ).…”
Section: Introductionmentioning
confidence: 99%